Tantangan Pendidikan Agama Islam dalam Menghadapi Gaya Belajar Generasi Z - Evi Febriani; Aghnia Sayyidatina; Aisya Mahda Ulya; Aisyah Radli; Anis Juliana Putri; Muhammad Kumaidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic education faces major challenges in adapting to social and technological changes, especially in dealing with the learning styles of Generation Z. Generation Z, born between the late 1997s and early 2012s, has unique characteristics, including dependence on technology, multitasking abilities, and a preference for interactive and digital media-based learning. This article aims to explore the challenges faced by Islamic education in responding to the learning styles of Generation Z, with a focus on curriculum adaptation, teaching methods, and the application of technology in the learning process. An innovative approach is needed to combine Islamic values with the learning needs of Generation Z, so that Islamic education can remain relevant and effective. This study also examines the role of teachers in guiding Generation Z to continue to understand and apply Islamic teachings in depth, even in this fast-paced digital era. The findings of this article are expected to provide insights and solutions for educators in facing these challenges, as well as contribute to the development of Islamic education that is more adaptive and responsive to the times.